Analysis of Risk Factors and Outcomes in Emergency Cesarean Sections: A One-Year Cross-sectional Study - Pandey, Sarita; Pandey, Sarika; Renu, Kumari; Sagar, Smriti (Journal of Neonatal Surgery, 2025)
Introduction: Emergency cesarean section (ECS) represent critical intervention in obstetric care with unique risk profiles. Understanding the relationship between specific indications and subsequent outcomes is crucial for optimizing clinical decision-making and resource allocation. Methods: This hospital-based cross-sectional study was conducted at a tertiary care teaching hospital over one year, including 294 women who underwent emergency cesarean section. Data was collected using a structured proforma capturing demographic details, obstetric history, indications, and outcomes. Results: The majority of women were 20-25 year age group(38.1%), from rural areas (59.2%), among which 33.3% were unbooked. Fetal distress (26.5%), non-progress of labor (17.7%), and failed induction (12.9%) were the leading indications. Category 2 emergencies (53.7%) predominated, followed by Category 3 (24.5%) and Category 1 (17.3%). Maternal complications included post-operative fever (14.6%), surgical site infections (10.5%), and postpartum hemorrhage (9.2%). Neonatal outcomes revealed 12.9% with 5-minute Apgar scores below 7 and 22.8% requiring NICU admission. Advanced maternal age, unbooked status, preterm delivery, Category 1 emergency classification, delayed intervention in urgent cases, antepartum hemorrhage, severe preeclampsia, and general anesthesia use emerged as an independent predictors of adverse outcomes. Conclusion: Significant maternal and neonatal morbidity was observed following emergency cesarean section. The study highlights critical areas for quality improvement, including strengthened antenatal care, standardized fetal monitoring protocols, optimized emergency workflows, and evidence-based management of high-risk conditions to improve maternal and neonatal outcomes in emergency obstetric care.